Vanguardism ideology and organization in totalitarian politics - Gray, Phillip W. (Phillip Wesley) 1978- (Routledge, 2020)
"Providing an innovative conceptualization to extremist political movements founded upon "world-historic" populations and vanguard party organizations, Vanguardism sets out a new path in investigating the intellectual and historical influences that created extremist politics, the totalitarian movements and regimes of the twentieth century, and a framework for interpreting extremism in the present. Expanding its view across the turbulent intellectual currents of the nineteenth century, Philip W. Gray illustrates how these ideas shaped the shared ideational and organizational structures that would develop into Leninism, Fascism, and Nazism in the early twentieth century. Moving beyond the Second World War, the book explicates how vanguardism did not vanish with the war's conclusion, but modified throughout the period of national liberation movements and Western extremist groups over the ensuing decades. Concluding in the present with an eye to the future, Gray presents a framework for comprehending the extremist movement of today, and how organizational shifts can give us clues to the forms of totalitarian politics of tomorrow. Original and provocative, Vanguardism will become essential reading for everyone looking to understand totalitarianism and extremist politics of our time"--